Modeling the demand across three major protein sources: Focusing on seafood protein. Issue 1 (2nd January 2023) - Park, Yeowoon; Joo, Hayeon; Moon, Junghoon
Abstract: Despite recent dramatic growth in seafood consumption worldwide, knowledge about seafood demand is limited relative to other protein sources. We model demand across three major protein categories (i.e., terrestrial meat, seafood, and plant-based protein) in South Korea to fill the research gap. This study models a quadratic almost ideal demand system (QUAIDS) by utilizing household panel data. The study takes this one step further by modeling demand within four seafood categories (i.e., fish, cephalopods, shellfish, and crustaceans). Sociodemographic variables, including health-related factors, are incorporated into the demand models. Results indicate that seafood is in a complementary relationship with terrestrial meat while it is a substitute for plant-based protein. All four seafood categories are a substitute for each other. The results reveal that people who take their health seriously tend to consume more seafood, particularly fish. The results have economic and marketing implications for which strategies could be adopted to influence seafood consumption.